E-Learning Di Sekolah Dasar: Tantangan Dan Peluang Berdasarkan Literature Review - Winanti Natasya Larosa; Noveri Amal Jaya Harefa (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the challenges and opportunities of implementing e-learning in elementary schools through a comprehensive literature review of recent academic sources. The research employs a thematic analysis approach to identify key patterns related to teacher readiness, student preparedness, parental involvement, and technological infrastructure availability. The findings indicate that e-learning implementation faces obstacles such as low teacher digital literacy, limited device and internet access, and the need for intensive guidance for young learners. However, e-learning also offers significant opportunities to enhance learning motivation through interactive media, strengthen digital literacy from an early age, and support more flexible and personalized learning experiences. This study highlights the importance of collaboration among schools, teachers, parents, and the government in optimizing e-learning implementation to improve the quality of elementary education in the digital era.